Effects of prolonged rest in hospitalized older adults - Ibarra Cornejo, José Luis (2018)
Introduction: Prolonged bed rest and decreased physical activity in the elderly represent a predisposing factor to the development or worsening of certain pathological conditions most closely related to the cardiovascular, respiratory and musculoskeletal systems. Functional impairment in less than the activities of daily living and increase by about 50% when they are over 80 years of age. Objective: To describe the main effects of bed rest on the main systems that could generate a functional decrease in the elderly hospitalized. Methodology: A bibliographic review was performed in Pubmed, Scielo and Pedro databases. Results: The information obtained was organized according to the body systems mainly involved in prolonged rest. It was found that the lack of mobility in older adults causes a physical deconditioning, in addition to an aggravation of the disease that leads to hospital residences with an increase in the days of hospitalization. Conclusions: bed rest can be minimized as much as possible and may prescribe an outpatient recovery and physical activity to limit the effects of deconditioning of bed rest.